Burosumab - new potent treatment for X-linked hypophosphatemia and tumor-induced osteomalacia - Wojtuś, Magda; Tomaszuk, Sebastian; Wąsik, Karolina (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Elevated FGF23 in X-linked hypophosphatemia (XLH) and tumor-induced osteomalacia (TIO) leads to systemic hypophosphatemia, several musculoskeletal manifestations and rickets in children. In this review we describe advances in the management of XLH and TIO using burosumab, which is a new therapeutic option approved both for adults and children. A search was conducted using PubMed and Google Scholarship databases. Brief description of the state of knowledge: Patients with XLH and TIO exhibit a similar clinical picture and way of treatment. Although in TIO surgery is the only definitive treatment, some tumors cannot be removed due to their location. In this case oral conventional therapy is used in treating both in TIO and XLH. Another approved treatment option is the use of burosumab, which is a fully humanised FGF23-antibody. This therapy led to normalisation of phosphate homoeostasis and resulted in improvement of bone turnover, fracture healing, subjective pain, and physical function. Compared to conventional, oral therapy burosumab has been shown to be superior for treatment of XLH and TIO. Conclusions: While burosumab appears to improve treatment outcomes, the effects of chronic or lifelong use have yet to be established. Long term follow-up studies would be necessary to assess especially the potential risk of nephrocalcinosis and cardiac calcification.